Creation of a multilingual aligned corpus with Ukrainian as the target language and its exploitation - Grabar, Natalia; Hamon, Thierry (National Technical University «KhPI», 2017)
The question on creation of linguistic resources (such as corpora, lexica or terminologies) occupies an important place in the research areas related to linguistics, Natural Language Processing, Computer Sciences, psycholinguistics, etc. In this paper, we propose the description of a multilingual corpus in which Ukrainian is the target language, while source languages are Polish, French and English. The corpus contains literary texts and a small subset built with texts provided by medical area. On the whole, the corpus is composed of 62 literary texts and 129 medical texts. The corpus counts over 1 million words in the tar-get Ukrainian language, and at least as much in the source languages taken all together. This is a directional corpus aligned at the level of sentences. After the description of this corpus, we introduce some possible exploitations and first results. We then conclude and indicate some directions for future work. The corpus presented in this work is available for the research purposes: http://natalia.grabar.free.fr/resources.php.